2009
DOI: 10.1177/1545109709341855
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Women With and Without HIV-1 Infection Attending an STI Clinic in Vitoria, Brazil

Abstract: We conducted a cross-sectional study in Vitória, Brazil, to assess the prevalence of human papillomavirus (HPV) infection in HIV-positive and HIV-negative women attending a sexually transmitted infection (STI)/AIDS clinic. We also investigated the presence of HPV genotypes and assessed covariates for HIV infection. Enrolled patients received a gynecological evaluation, and cervical scrape samples were collected for cytological analysis and HPV-DNA polymerase chain reaction (PCR). A blood sample was obtained to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…These results underscore the importance of routine gynecologic examinations and follow-up in those who present with cervical lesions. These results are in agreement with other Brazilian 10 , 20 , 21 , 22 , 23 and international studies 12 , 13 , 14 , 24 , 25 that showed high prevalence of high risk HPV among HIV infected women.…”
Section: Discussionsupporting
confidence: 93%
“…These results underscore the importance of routine gynecologic examinations and follow-up in those who present with cervical lesions. These results are in agreement with other Brazilian 10 , 20 , 21 , 22 , 23 and international studies 12 , 13 , 14 , 24 , 25 that showed high prevalence of high risk HPV among HIV infected women.…”
Section: Discussionsupporting
confidence: 93%
“…The global estimates of HPV prevalence among HIV-infected women have varied by region and the level of the HIV epidemic. [13] Studies in HIV-infected women from countries with generalized HIV epidemics, particularly in Africa, have reported a high (45–90%) carcinogenic HPV prevalence [14] , [15] , [16] , [17] while studies from concentrated or low-level HIV epidemics in Asia, including those from India [4] , [5] , [18] , [19] , Latin America [20] , [21] , Europe [22] , [23] , and North America [24] , [25] have reported lower (20–40%) carcinogenic HPV prevalence rates among HIV-infected women. The differences in HPV prevalence in different geographical locales may be attributed to differing behavioral and immunological status of the participants, as well as the differences in primers and sensitivity of the assays used for PCR.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the low prevalence of high-grade SIL might be due to earlier access to healthcare and prompt diagnosis, thereby avoiding occurrences of high-grade SILs. 12 …”
Section: Discussionmentioning
confidence: 99%